A rare case of streptococcal pharyngitis in an adult male causing hemophagocytic lymphohistiocytosis - Narula, Shubhank; Agarwal, Pankaj Kumar; Garg, Ambuj (Indian Journal of Case Reports, 2024)
Hyperinflammatory responses due to cytokine storms involve multiple systems in hemophagocytic lymphohistiocytosis (HLH) leading to morbidities. Multiple bacterial etiologies have been suggested as a cause of secondary HLH but streptococcal infection has only been reported in pediatric cases. Streptococcus has been considered a notorious pathogen due to its ability to interfere with host immunity through the phenomenon of molecular mimicry. This case report shows the sequence of events post-streptococcal pharyngitis in a 28-year-old male, which lead to HLH and fatality to life, and how a timely intervention of steroids salvaged the patient.